(untitled) - HONZÍKOVÁ, Jarmila (Trends in education, 2008)
Article presents concrete sorts test, which it is possible use at testing nonverbal creativity. For research creative ability are most often exploitation TDS test, the Torrence Figural tests are exploitation for the creative ability research and the Pattern Assembly Test was used to establish the level of technical imagination.
Keywords: testing; nonverbal creativity